Preliminary study on cells viability based on toxicity effect of varnish fluoride made from Indonesian de-waxed shellac - Djustiana, Nina; Takarini, Veni; Hasratiningsih, Zulia (Padjadjaran Journal of Dentistry, 2019)
Introduction: Varnish fluoride has the ability to prevent enamel demineralization. De-waxed shellac that mostly used for fruits coating, now is applied as varnish fluoride materials. This de-waxed shellac is quite potential since the product can be found from Indonesian sources. The research aims to describe the toxicity effect of varnish fluoride made of de-waxed shellac by measuring the viability of the fibroblast cells. Methods: The research method that was used in this study is in vitro experimental method, which using the tooth that had been smeared with varnish fluoride contacted with fibroblast cells REF (Rat Embryonic Fibroblast) for 4, 8, and 24 hours. The toxicity effect of varnish fluoride was then measured by cell viability. Results The results show that the average cells viability on 4 hours contacted tooth was 88%, while average cells viability on 8 hours contacted tooth was 74%, and lastly the average cells viability on 24 hours contacted tooth was 63%. Conclusion: The conclusion of this preliminary study on cells viability based on toxicity effect of varnish fluoride made from Indonesian de-waxed shellac are different based on contacted time.Keywords: Cell viability, toxicity effect, varnish fluoride, Indonesian de-waxed shellac